#TITLE_ALTERNATIVE# - KAUTSAR BAKHTIE (NIM : 13707044); Dosen Pembimbing : Dr. Ir. Hermawan Judawisastra, FAJRI
Waste from conventional composites generates the development of Eco-Composites. One type of Eco-Composites is composite thermoplastic with natural fiber reinforcement. Natural fiber has been chosen because it has CO2 free characteristic. The problem of using natural fibers is it is difficult to bind with the matrix and binds easily with water. One type of chemical treatment to improve the properties of natural fibers is permanganate treatment. This study will be conducted for the optimization of permanganate treatment to tensile strength and water absorption properties of kenaf-polypropylene (PP) composites. The tensile strength data will be compared with the model. The composites were made of uni directional kenaf fiber and PP wastes by means of compression molding at 185oC. Variations in the chemical treatments are no treatment, alkali treatment, and permanganate treatment with four different weight concentrations: 0.01%, 0.02%, 0.03% and 0.05%. Tensile tests were conducted before and after water absorption test of the composites. Water absorption test was conducted according to ASTM D570 Ã‚Â– 98. The physical properties of composites were characterized to obtain the volume fraction of constituent materials and void. Fracture surface of composites was observed by means of Scanning Electron Microscopy technique. The maximum strength of 125 MPa was obtained for PP-kenaf composites at optimum concentration of 0.02%wt permanganate treatment. The composite strength increased by 38% compared to composites without treatment. Permanganate treatment decreased the water absorption properties of PP-kenaf composites. The minimum water absorption (16.55% in weight) obtained by permanganate treatment with concentration 0.05%wt. It seems like permanganate treatment did not decrease the diffusivity of composite. Permanganate treatment increased the water resistance of PP-kenaf composites. Permanganate treatment with concentration 0.01% by weight resulted the least reduced strength, 55% decrease compared to the untreated composites before water absorption test). This is due to the least interface damaged after 0.01%wt permanganate treated compared to other composites. The model that has most close results compared to the experiment is a model of rule of mixture with an average percentage difference of 6.34%.